Genetics and evolutionary aspects of the Apertados Canyons Geosite, in the Seridó UNESCO Global Geopark, NE Brazil - Dantas, Assucena Nogueira Batista; Cordeiro, Abner Monteiro Nunes; Bastos, Frederico de Holanda; Lopes, Davi do Vale; Nascimento, Marcos Antônio Leite do; Maia, Rubson Pinheiro (Revista Brasileira de Geomorfologia, 2025)
This paper reports and analyze the transverse drainage process responsible for the sculpting of the Apertados Canyon (Seridó UNESCO Global Geopark), located in the northern portion of the Umburanas Mountain Range, in Northeastern Brazil. Morphological and lithostructural evidence of superimposition was obtained through remote sensing (e.g., extraction of structural lineaments, drainage network, slope) and field work. Remnants of an agradational paleosurface were observed in the Picuí River basin area; the presence of other transverse drainages (water gaps) cutting the same topographic barrier; and orthogonal inflections of river courses. This evidence allowed us to deduce that the superimposition drainage mechanism was responsible for the formation of the Cânion dos Apertados. This mechanism was influenced by changes in regional base level, climatic oscillations and tectonic reactivations, observed from the Middle Miocene onwards, resulting from W-E and NW-SE compressive efforts, along the deformation structures.